Athanasios af Alexandrias 39. Påskebrev fra påsken 367: Introduktion og oversættelse til dansk Introduktion og oversættelse til dansk - Pedersen, Nils Arne (Dansk teologisk tidsskrift, 2020)
This is the first translation into Danish of the Coptic Sahidic version of Athanasius’ famous 39th Festal Letter from AD 367, which established the Biblical Canon and contained for the first time precisely those 27 New Testament scriptures which are still the Christian norm today. The translation is introduced, annotated, and based on the two existing Coptic manuscripts. The Greek excerpt of a part of the Festal Letter is also translated.